Incision by UvrABC excinuclease is a step in the path to mutagenesis by psoralen crosslinks in Escherichia coli. - Sladek, F M (1989)
4,5',8-Trimethylpsoralen (psoralen) plus near UV light produces interstrand crosslinks and monoadducts in DNA, both of which are mutagenic. In Escherichia coli, crosslinks are incised by UvrABC excinuclease, an event that can lead to homologous recombination and repair. To determine whether UvrABC incision of crosslinks is a step in the path to mutagenesis as well as repair, the effect of DNA homologous to a target gene on a plasmid was determined. pSV2-gpt DNA was treated with psoralen and transformed into a pair of hosts: one was gpt+, the other was delta (gpt-lac)5. The DNA was extracted and transformed into a tester strain [delta (gpt-lac)5] in which Gpt- mutations in the plasmid were scored. The results show that psoralen-induced mutations were reduced to background levels by the presence of the gpt+ homolog in the host chromosome. delta gpt hosts that were constitutively induced for the SOS response yielded point mutations, whereas noninduced hosts yielded almost exclusively large deletions. Since crosslinks were estimated to be responsible for most of the mutations observed, we conclude that the premutagenic lesion of psoralen crosslinks is recombinagenic and therefore very likely to be the product of UvrABC incision.